III. The Question of Symmetry - Lerner, A. P. (Review of Economic Studies, 1936)
Journal Article Further Notes on Elasticity of Substitution: III. The Question of Symmetry Get access A. P. Lerner A. P. Lerner Leon Fellow of the University of London London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 2, February 1936, Pages 150–151, https://doi.org/10.2307/2967508 Published: 01 February 1936